2021
DOI: 10.3390/nu13103504
|View full text |Cite
|
Sign up to set email alerts
|

Which Diets Are Effective in Reducing Cardiovascular and Cancer Risk in Women with Obesity? An Integrative Review

Abstract: Women are more affected by obesity than men which increases their risk of cancer and cardiovascular disease (CVD). Therefore, it is important to understand the effectiveness of different types of diet in the context of women’s health. This review aims to summarize the scientific evidence on the effects of different types of diet for women with obesity and their impact on CVD and cancer risk. This review included epidemiological and clinical studies on adult women and different types of diets, such as the Medit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 133 publications
(231 reference statements)
0
8
1
1
Order By: Relevance
“…In addition, we report an association among the observance of Ramadan and the presence of elevated W/Hp ratio and visceral fat, variables which have been shown to be associated with cardiometabolic risk factors [ 29 ]. These results are not in agreement with those of Silveira et al [ 30 ] and Yang et al [ 31 ], who reported that intermittent fasting had positive effects on reducing cardiovascular risk factors in obese women. These differences are probably due to the non-compliance with dietary recommendations by the participants of our study, which have been previously discussed.…”
Section: Discussioncontrasting
confidence: 96%
“…In addition, we report an association among the observance of Ramadan and the presence of elevated W/Hp ratio and visceral fat, variables which have been shown to be associated with cardiometabolic risk factors [ 29 ]. These results are not in agreement with those of Silveira et al [ 30 ] and Yang et al [ 31 ], who reported that intermittent fasting had positive effects on reducing cardiovascular risk factors in obese women. These differences are probably due to the non-compliance with dietary recommendations by the participants of our study, which have been previously discussed.…”
Section: Discussioncontrasting
confidence: 96%
“…Because foods and/or nutrients may interact with each other, inaccurate conclusions may result. 48–50 It appears that an inverse association between the MIND diet and the CVD incidents in the present study could be attributed to the synergistic effects of MIND diet components.…”
Section: Discussionmentioning
confidence: 57%
“…Results of the pooled analysis of longitudinal studies revealed that high adherence to MedDiet reduced the risk of global cognitive decline in non-demented older adults. However, no significant associations between MedDiet adherence and the incidence of mobility problems, mild cognitive impairment, and dementia were found Yes Quintela BC et al [ 37 ] 2021 24 Observational PubMed Embase eGFR Proteinuria New Castle Ottawa scale (NOS) for cohort studies The consumption of fruit, vegetables and dietary fiber (DASH and MedDiet) revealed low risk associations for chronic kidney disease, being recommended models to reduce the occurrence and progression of the disease No Silveira EA et al [ 38 ] 2021 7 RCT, cohort PubMed Scopus Scielo Web of Science Body Mass Index Body fat Blood pressure Fasting Blood Glucose C-Reactive Protein Total Cholesterol NR The MedDiet had beneficial changes in weight loss and maintenance, reduction of body fat and inflammatory factors. MedDiet had greater long-term favorable effects on CVD risk factors like BMI, blood pressure, fasting blood glucose, total cholesterol and inflammatory markers such as CRP in individuals with obesity No Gibbs J et al [ 39 ] 2021 41 RCT MEDLINE Embase Web of Science Systolic blood pressure Diastolic blood pressure RoB-2: a revised tool for assessing risk of bias in randomized trials Consumption of the Mediterranean diet was associated with a mean reduction in SBP and DBP compared with the consumption of comparator diets Yes Kadam I et al [ 40 ] 2021 20 Observational PubMed CINAHL Scopus Body Mass Index Waist circumference NIH Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies ...…”
Section: Resultsmentioning
confidence: 99%